Diagnostic methods for epidemiological studies of tropical theileriosis (Theileria annulata infection of cattle) - Ílhan, Tülín (The University of Edinburgh, 2000)
The aim of this study was to develop improved diagnostic techniques for tropical theileriosis caused by T. annulata. These were (i) stage specific indirect enzyme-linked immunosorbent assays (ELISA) to distinguish animals vaccinated with high passage cell lines from those naturally infected in the field and (ii) a highly sensitive and specific polymerase chain reaction (PGR) methodology to detect low level infections in carrier animals.

Material for this study was provided by experiments in which calves were infected in different ways to simulate the field situation. Three groups of animals were infected with different life cycle stages of T. annulata: sporozoites, a low passage macroschizont-infected cell line or a high passage (attenuated) cell line, normally used as a vaccine to control tropical theileriosis, and challenged with virulent heterologous sporozoites. The challenge indicated that different parasite stages and levels of attenuation used for primary infection stimulated different levels and duration of immunity. The immunity stimulated by sporozoites and the low passage cell line was solid throughout the study, in contrast to immunity induced by the high passage cell line which fell by seven months post-infection. The carrier status of these animals was determined by PCR using primers from small subunit ribosomal RNA (ssu rRNA) in comparison to that illustrated by microscopic detection of piroplasms and cell culture isolation of macroschizonts. The different patterns revealed that calves infected with sporozoites or the low passage cell line were persistent carriers, while those inoculated with the high passage cell line were intermittent or only transient carriers.

In order to obtain an antigen expressed by the macroschizont stage of the parasite to use in ELISA an attempt was made to isolate a T. annulata gene, which was a homologue of the QP rich protein of T. parva, from a T. annulata ZAP cDNA library. Three T. annulata genes, NCI, NC2 and NC10, were isolated from the cDNA library by screening with QP cDNA probe. Characterisation of these genes was carried out by Southern, northern, western blot and sequence analyses. An immunogenic recombinant protein, NC10-Sspl3, was obtained from the NC10 gene which was expressed by the xi macroschizont stage of the parasite. Antisera against the NC10-Sspl3 antigen detected polypeptides both in macroschizonts and host nucleus.

Indirect ELISA using recombinant antigens, a merozoite rhoptry recombinant antigen (Tamr-1), NC10-Sspl3 and an antigen expressed by both the macroschizont and piroplasm stages of the parasite, Tash-2, were standardised following international guidelines on data expression and quality assurance. The results were compared with those obtained with indirect immunofluorescence antibody test (IFAT) using piroplasm antigen. The recombinant antigens, Tamr-1, NC10-Sspl3 and Tash-2, were screened against antisera produced by infection of cattle with different life cycle stages of T. annulata in order to examine whether the combination of the Tamr-1 and NC10-Sspl3 ELISAs or Tamr-1 and Tash-2 ELISAs would distinguish vaccinated animals from those that are naturally infected. The result showed that both Tamr-1 and Tash-2 antigens sensitively detected the antibodies in animals infected with both sporozoites and the low passage cell line. No antibody responses were detected against the Tamr-1 antigen, and were very low against the Tash-2 antigen in animals immunised with the high passage cell line. The antibody responses detected by the NC10-Sspl3 ELISA were lower than those obtained for both Tamr-1 and Tash-2 ELISAs.

The results of this study show that, ELISAs using the Tamr-1, NC10-Sspl3 or Tash-2 recombinant antigens did not reliably distinguish animals vaccinated with the high passage cell line from those that were naturally infected. Both Tamr-1 and Tash-2 ELISAs, however, could serve as powerful diagnostic tools in epidemiological studies of theileriosis, as ELISA systems permit processing of larger numbers of samples than IFAT and give objective results.

The nested PCR using primers derived from the gene encoding the 30 kDa major merozoite surface antigen (Tarns-1) of T. annulata amplified parasite DNA in blood samples from animals exhibiting low piroplasm parasitaemia. The PCR distinguishes T. annulata from T. buffeli in cattle and T. annulata from T. lestoquardi and B. equi in vector ticks. Such sensitive and specific tests would complement the seroepidemiological studies of theileriosis and help to target the vaccine produced.